Penggunaan Model Project Based Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Di Sekolah Dasar - Hardiansyah, Framz; Latifa, Addya (Science and Education Journal (SICEDU), 2024)
This study aims to improve the critical thinking skills of the fourth grade students of IV UPT SD Negeri 008 Langgini Sendayan for the academic year 2023/2024, which consists of 15 students. This research method is Classroom Action Research (CAR) which is carried out in two learning cycles. Each cycle consists of two meetings and four stages of learning, namely: planning, implementation, observation, and reflection. The time of the study was carried out in may 2024. Data collection techniques were in the form of documentation, observation and tests. The results of the critical thinking skills of fourth grade studentss of IV UPT SD Negeri 008 Langgini in pre-action with an average value of 52,27 with a learning completeness percentage of 27%. In cycle 1 meeting, 1 the average value 60,27 with a learning completeness percentage of 41% and in the first cycle of the second meeting, there was increase with an average value of 67,5 with a learning mastery percentage of 50%. In the second cycle of the first meeting, it also increased with an average value of 74,54 with a learning mastery percentage of 77%, and in cycle 2, the second meeting increased again with an average value of 81,59 with a learning completeness percentage of 86%. Thus, it can be concluded that by applying the Project Based Learning model, it can improve the critical thinking skills of fourth grade students at IV UPT SD Negeri 008 Langgini.